Synopsis of proposals on fungal nomenclature: a review of the proposals concerning Chapter F of the International Code of Nomenclature for algae, fungi, and plants submitted to the XII International Mycological Congress, 2024 - Tom W. May; Konstanze Bensch (IMA Fungus)
Abstract A commentary is provided on the seven formally published proposals to modify the provisions of Chapter F of the International Code of Nomenclature for algae, fungi, and plants (ICNafp) that will be dealt with by the Fungal Nomenclature Session (FNS) of the 12th International Mycological Congress (IMC12) in August 2024. The proposals deal with: fungi whose morph-names have the same epithet; the listing of synonyms under entries for protected names in the Code Appendices; the processes of protection and rejection; the use of DNA sequences as nomenclatural types; the use of genomes as nomenclatural types; and the designation of fungi known only from DNA sequences. Information is also provided on the composition and role of the Fungal Nomenclature Bureau, the operation of the FNS and the pre-Congress Guiding vote.